Pengaruh Manajemen Pelayanan dan Produktivitas Kerja Pegawai Terhadap Akreditasi UPT Puskesmas Segala Mider Bandar Lampung - Oktalisya, Vina; Ardansyah (Jurnal EMT KITA, 2023)
This study aims to study the influence of labor productivity and service management on accreditation at UPT Puskesmas Sangat Mider Bandar Lampung. The method used in this study was a survey and descriptive quantitative analysis with the participation of 42 respondents. The results of the discussion show that the accreditation of All Mider Bandar Lampung Community Health Center has had a significant impact on the productivity of staff and public health service management.  The conclusion of this article asserts that improving public health service policies in community health centers and increasing workforce productivity can contribute significantly to achieving accreditation outstanding.